Ehrlichia effector SLiM-icry: Artifice of cellular subversion - Pittner, Nicholas A.; Solomon, Regina N.; Bui, Duc-Cuong; McBride, Jere W. (Frontiers in Cellular and Infection Microbiology, 2023)
As an obligately intracellular bacterial pathogen that selectively infects the mononuclear phagocyte, Ehrlichia chaffeensis has evolved sophisticated mechanisms to subvert innate immune defenses. While the bacterium accomplishes this through a variety of mechanisms, a rapidly expanding body of evidence has revealed that E. chaffeensis has evolved survival strategies that are directed by the versatile, intrinsically disordered, 120 kDa tandem repeat protein (TRP120) effector. E. chaffeensis establishes infection by manipulating multiple evolutionarily conserved cellular signaling pathways through effector-host interactions to subvert innate immune defenses. TRP120 activates these pathways using multiple functionally distinct, repetitive, eukaryote-mimicking short linear motifs (SLiMs) located within the tandem repeat domain that have evolved in nihilo. Functionally, the best characterized TRP120 SLiMs mimic eukaryotic ligands (SLiM-icry) to engage pathway-specific host receptors and activate cellular signaling, thereby repurposing these pathways to promote infection. Moreover, E. chaffeensis TRP120 contains SLiMs that are targets of post-translational modifications such as SUMOylation in addition to many other validated SLiMs that are curated in the eukaryotic linear motif (ELM) database. This review will explore the extracellular and intracellular roles TRP120 SLiM-icry plays during infection - mediated through a variety of SLiMs - that enable E. chaffeensis to subvert mononuclear phagocyte innate defenses.